2008
DOI: 10.1016/j.ergon.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of colour preattentive processing in human–computer interaction task efficiency: A preliminary study

Abstract: In this paper, results of experimental research on the preattentive mechanism in the humancomputer interaction (HCI) were presented. Fifty four subjects were asked to find interface elements from various panel structures. The arrangements were differentiated by their orientation (vertical, horizontal), colour pattern (ordered, unordered) and object background colours (green-blue, green-red, blue-red). The main finding of the study generally confirms the profits provided by the visual preattentive processing of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…The recorded mean error rate in this research (2.4%) was generally comparable to the values obtained in other research. For example, in the research of Schaik & Ling (2001), Pearson & Schaik (2003), Grobelny et al (2005), Michalski et al (2006), Michalski & Grobelny (2008), the mistakes occurred in less than 3% of all trials.…”
Section: Incorrect Selectionsmentioning
confidence: 98%
See 1 more Smart Citation
“…The recorded mean error rate in this research (2.4%) was generally comparable to the values obtained in other research. For example, in the research of Schaik & Ling (2001), Pearson & Schaik (2003), Grobelny et al (2005), Michalski et al (2006), Michalski & Grobelny (2008), the mistakes occurred in less than 3% of all trials.…”
Section: Incorrect Selectionsmentioning
confidence: 98%
“…Although currently there exist many other methods, the direct manipulation is still one of the most popular, especially among graphical interfaces. The study described in this publication may be situated in the trend of research related both to visual search and visually controlled motor activity (compare Grobelny et al, 2005;Michalski et al, 2006;Michalski & Grobelny, 2008). This area is a combination of the traditional Fitts' approach (Fitts, 1954;Fitts & Peterson, 1964), in which only the movement time related to graphical object selection is taken into account, and the situation where the time of visual search for a particular target among the group of distractors is of a main concern.…”
Section: Introductionmentioning
confidence: 99%
“…This may have allowed participants using the grey interface to focus on more relevant information. Previous research conducted by Michalski and Grobelny in 2008 investigated the effects that object background color had on search times. They found that certain color contrasts had an effect on task time as the objects were less salient but they found higher contrasting colors had shorter task times over the grey panel.…”
Section: Discussionmentioning
confidence: 99%
“…Human visual ability is required for visual search tasks ranging from industrial inspection work, military target acquisition, to video display tasks (Drury and Prabhu, 1994;Pearson and Schaik, 2003;Marmaras et al, 2008;Michalski and Grobelny, 2008). The visual search process has been described as a series of visual lobe (useful visual field) placements in a search field aiming at target detection (Drury, 1990).…”
Section: Introductionmentioning
confidence: 98%